Digital transformation of global business processes: the role of dual embeddedness. Issue 2 (23rd September 2019) - Ekman, Peter; Thilenius, Peter; Thompson, Steven; Whitaker, Jonathan
Abstract : Purpose: While much existing research on multinational corporation (MNC) digital transformation has followed a linear design and implementation logic using cross-sectional data, the multiple and divergent needs of headquarters (HQ) and subsidiaries suggest that MNC digital transformation actually involves a more iterative journey. The purpose of this paper is to apply the theoretical perspective of embeddedness to better define the complexities of MNC digital transformation, and identify how HQ and subsidiaries can navigate the complexities. Design/methodology/approach: This paper presents a longitudinal multi-case study of five Forbes Global 2000 firms that are HQ in Europe with large subsidiaries in the USA. The authors conducted in-depth interviews with 26 senior executives at HQ and subsidiaries over a 15-month period. Findings: The process of digital transformation is significantly influenced by internal embeddedness (relationship of HQ with subsidiaries and across subsidiaries) and external embeddedness (relationship of subsidiaries with their local markets), and also by strategy, financial and technology considerations. While HQ and subsidiaries have different perspectives, an understanding of these influences can help HQ and subsidiaries navigate digital transformation. Research limitations/implications: HQ and subsidiaries can apply insights from this research to navigate the complexities of digital transformation. Originality/value: This paper demonstrates that embeddedness is a useful theory to understand the complexities of MNC digital transformation.